The Obedience of woman pregnant in consuming Kalk Dose 1500 mg/day to reduce hypertension In The Trimester III - Sehmawati; Pintam Ayu Yastirin (LPPM AN NUUR, 2021)
Background: Hypertension in pregnancy occurs around 5-15%, and is one of 3 causes of maternal mortality and morbidity in addition to infection and bleeding. Hypertension in pregnancy can also progress to preeclampsia and eclampsia which can cause maternal and fetal death, Compliance as the level of the patient performs the manner of treatment and behavior suggested by his physician or the other. Obedience is the patient's positive behavior in achieving the goal of therapy. Purpose: To know maternal obedience consumption of calcium dose 1500mg / day to decrease of hypertension. Method: This research is correlative analytics using 32 pregnant women with hypertension. Each responden was given a questionnaire containing about maternity compliance consumption of calcium dose 1500mg / day. Bivariate analysis using the Chi Square test. Results: 23 respondents were found to be obedient to calc intake, 22 respondents experienced a decrease in blood pressure and 1 respondent did not experience a decrease in blood pressure. Of the 9 respondents who did not comply with calc consumption, 7 respondents did not experience a decrease in blood pressure, 2 respondents experienced a decrease in blood pressure. Conclusion: There was a relationship between maternal adherence to the consumption of 1500 mg/day calk to decrease blood pressure in third trimester pregnant women (p = 0.000 or p <0.05)